Pengembangan kriya perca kolaborasi ragam hias Bintang Na Toras Mandailing dan bunga teratai Cina - Juliana, Netty (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2024)
Student creativity activities in industrial engineering lectures are in the form of developing patchwork dining table cloths in collaboration with the Na Toras Mandailing Star and Chinese Lotus Flowers. The purpose of this activity is to improve students' knowledge and skills in designing home industries, especially handicrafts on household linen. The methodology used in this scientific work is in the form of a qualitative explosive method. There are several stages in the process of the handicraft home industry, namely; 1) Able to create a concept map of the organizational structure of the home-based craft industry, 2) Able to create a craft-pattern design concept, 3) Able to develop manual drawing sketches, 4) Able to create innovative motifs, and 5) Able to apply motifs to cloth-pattern crafts dining table. This scientific work produces an ethnic and innovative form of home industry design for handicrafts on the dining table cloth. Keywords: Development, craft, patchwork, Mandailing, China.